2017
DOI: 10.1186/s13643-017-0568-6
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of interventions to increase awareness of mental health and well-being in athletes, coaches and officials

Abstract: BackgroundThe aim of the current study was to conduct a systematic review determining the effect of sport-specific mental health awareness programs to improve mental health knowledge and help-seeking among sports coaches, athletes and officials. The second aim was to review the study quality and to report on the validity of measures that were used to determine the effectiveness of programs.MethodsSport-specific mental health awareness programs adopting an experimental or quasi-experimental design were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
134
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(140 citation statements)
references
References 77 publications
5
134
0
1
Order By: Relevance
“…Los resultados de este trabajo están en la línea de lo encontrado en la literatura científica en estos últimos años, resaltando la gran importancia que tiene la intervención psicológica en el deporte, proporcionando un mayor bienestar psicológico y un incremento del rendimiento deportivo (Breslin, Shannon, Haughey, Donnelly y Leavey, 2017;Brown y Fletcher, 2017;Golby y Wood, 2016;Gross et al, 2018). Además, también está en la línea de aquellos estudios que han mejorado, a través del entrenamiento psicológico, variables psicológicas como la motivación, la concentración, la autoconfianza o el nivel de activación (Beckmann and Elbe, 2015;Olmedilla and Domínguez-Igual, 2016), o los recursos y la adquisición de habilidades psicológicas (técnicas, estrategias, etc.)…”
Section: Discussionunclassified
“…Los resultados de este trabajo están en la línea de lo encontrado en la literatura científica en estos últimos años, resaltando la gran importancia que tiene la intervención psicológica en el deporte, proporcionando un mayor bienestar psicológico y un incremento del rendimiento deportivo (Breslin, Shannon, Haughey, Donnelly y Leavey, 2017;Brown y Fletcher, 2017;Golby y Wood, 2016;Gross et al, 2018). Además, también está en la línea de aquellos estudios que han mejorado, a través del entrenamiento psicológico, variables psicológicas como la motivación, la concentración, la autoconfianza o el nivel de activación (Beckmann and Elbe, 2015;Olmedilla and Domínguez-Igual, 2016), o los recursos y la adquisición de habilidades psicológicas (técnicas, estrategias, etc.)…”
Section: Discussionunclassified
“…Two were not influenced by energy balance, although they tried to eat healthy. The instructors were aware of the need for biological regeneration, and mostly they chose: stretching and "rolling" (8), sauna (6), massage (4), water baths (1). One of the respondents did not use biological regeneration treatments.…”
Section: Resultsmentioning
confidence: 99%
“…Analysing the survey results, it can be concluded that most of the instructors feel overtraining manifested in the lack of post-workout regeneration (10) and a feeling of skeletal muscles stiffness and pain (8), despite the appropriate amount of sleep and the use of biological regeneration treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide range of stressors were identified in studies with athletes including stressors outside of sports as well as sport-specific, competition-specific, and other sport-related stressors (Beckmann and Ehrlenspiel, 2017; Ehrlenspiel et al, 2017; Gustafsson et al, 2017; Sallen, 2017; Tranaeus et al, 2017). The findings that stress research has generated in the field of competitive sports encourage efforts to develop and implement educational psychology interventions for athletes, to help them improve their personal stress resistance and prevent stress-related impairment of their health and performance (Rumbold et al, 2012; Stambulova, 2016; Breslin et al, 2017; Sallen et al, 2017; Schinke et al, 2017). Instruments for stress assessment are of great importance in this context.…”
Section: Introductionmentioning
confidence: 99%